Principal's Transformational Leadership in English Language Habituation Program for SDN 1 Kemuning Students - Luthfiyani, Nur Azizah; Ahmad Suriansyah; Arta Mulya Budi Harsono; Rizky Amalia; Muhammad Ziyan Takhqiqi Arsyad; Novitawati (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
This study examines the role of the principal's transformational leadership in promoting the habitual use of English in the school environment among elementary school students.  This research utilizes a qualitative method for data analysis, encompassing thematic organization and data triangulation. Qualitative methods were used to examine interview data.  The findings reveal that the principal of SDN 1 Kemuning demonstrates a clear vision to improve students' English proficiency, motivates and inspires teachers and staff to support the program, fosters effective communication and collaboration, and empowers and develops teachers and staff. The English language habituation program is systematically integrated into every aspect of school life, employing engaging and creative teaching methods and receiving adequate resource support. This research found a positive impact on students' English language abilities, evident in improved listening and speaking skills, and increased self-confidence.  However, challenges remain, including teachers' English proficiency, limited learning resources, and constraints on teachers' time and energy.  Recommendations include enhancing teachers' English proficiency, enriching learning activities, increasing parental involvement, and educating parents about the importance of using English in daily life.